The Effect of Transformational Leadership Style and Work Communication on Employee Performance in Molding Department PT. FCC Indonesia - Farhabi Ahmad Noor; Asep Jamaludin; Nandang Nandang (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study aims to determine the effect of transformational leadership and the effectiveness of work communication on the performance of PT FCC Indonesia's employees at the Molding Department. The research design used a quantitative approach by collecting data through distributing questionnaires. The sample in this study were 99 employees of the Molding Department of PT FCC Indonesia. Methods of data analysis using Multiple Regression analysis assisted by SPSS 26. The results showed that Transformational Leadership Style has a partially significant effect on Employee Performance, Work Communication partially has a significant effect on Employee Performance, Transformational Leadership Style has a greater influence on Employee Performance than Work Communication and Transformational Leadership Style and Work Communication simultaneously have a significant effect on Employee Performance.